2015
DOI: 10.1073/pnas.1419677112
|View full text |Cite
|
Sign up to set email alerts
|

Essential genome of Pseudomonas aeruginosa in cystic fibrosis sputum

Abstract: Defining the essential genome of bacterial pathogens is central to developing an understanding of the biological processes controlling disease. This has proven elusive for Pseudomonas aeruginosa during chronic infection of the cystic fibrosis (CF) lung. In this paper, using a Monte Carlo simulation-based method to analyze high-throughput transposon sequencing data, we establish the P. aeruginosa essential genome with statistical precision in laboratory media and CF sputum. Reconstruction of the global requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
491
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 367 publications
(526 citation statements)
references
References 45 publications
17
491
0
Order By: Relevance
“…We then compared the expected to the observed data and observed that the fold changes in mutant abundance per gene follow typical (41,48) bimodal distributions (Fig. 1A).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…We then compared the expected to the observed data and observed that the fold changes in mutant abundance per gene follow typical (41,48) bimodal distributions (Fig. 1A).…”
Section: Resultsmentioning
confidence: 97%
“…1A). These numbers are [41] and 358 in Haemophilus influenzae [42]). The core A. actinomycetemcomitans essential genome.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…A follow up study rectified these issues, incorporating these components into SCFM. Using Tn-seq (which is a more precise way to measure fitness, compared to RNA-seq), it was shown that near identical selection pressures exist between synthetic and expectorated CF sputum [128]. In a separate study, the use of an artificial sputum media was shown to increase diversity within a population, something not observed in Lysogeny Broth (LB) [108].…”
Section: In Vivo Conditions In Vitro Methodsmentioning
confidence: 99%